Bilateral Carotid Artery Occlusion and Cochlear Oxidative Stress and Hearing Loss in Rats - Hamed Fanaei; Akram Pourbakht; Sadegh Jafarzadeh (Basic and Clinical Neuroscience, 2020)
Introduction: This study aimed to evaluate the effects of bilateral carotid artery occlusion on cochlear oxidative stress and hearing status in rats. Methods: The rats were divided into two sets. The first set was used for electrophysiological recording (click and 4 kHz tone burst auditory brainstem responses and electrocochleography) on the day before surgery and then on the first, fourth, and seventh days after surgery. Animals of the second set were used for biochemical analysis. The cochlea of animals in the second set was collected on the first, fourth, and seventh days after carotids occlusion for biochemical analysis. For the control groups, no carotids occlusion was done. For ischemia induction, both common carotid arteries were occluded for 20 minutes. Results: Electrophysiological analysis showed that burst auditory brainstem thresholds signiﬁcantly elevated after common carotid arteries occlusion on the first, fourth, and seventh days after surgery with abnormal electrocochleography results at 75%, 70%, and 85% on the first, fourth, and seventh days after surgery, respectively. The electrophysiological finding confirmed by biochemical results that showed malondialdehyde and nitric oxide levels increased and superoxide dismutase and catalase activities decreased after occlusion in cochlea tissue. Conclusion: This study showed that bilateral common carotid artery occlusion increases cochlear oxidative stress and induces hearing loss in rats.